2012
DOI: 10.1155/2012/317504
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Procalcitonin in the Diagnosis of Appendicitis in Children: A Pilot Study

Abstract: Objective. To assess the predictive value of procalcitonin in detecting acute appendicitis (AP) in children, and to determine a cutoff value of procalcitonin which can safely include/exclude the diagnosis of acute appendicitis in children with acute abdominal pain. Methods. Prospective cohort study of children aged 5–17 years presenting to the emergency room with right lower quadrant (RLQ) tenderness and strong suspicion for acute AP. In addition to standard diagnostic workup for acute AP, a quantitative proca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The weighted prevalence of AA was significantly (p < 0.001) higher in studies that used either “abdominal pain suspected of AA” or “right lower quadrant (RLQ) pain” as their inclusion criteria (19 studies, n = 7,510, AA prevalence = 42.8%, 95% CI = 41.7–43.9) compared to those that used “abdominal pain” or undifferentiated abdominal pain (two studies, n = 1,095, AA prevalence = 13.4%, 95% CI = 11.5–15.6).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The weighted prevalence of AA was significantly (p < 0.001) higher in studies that used either “abdominal pain suspected of AA” or “right lower quadrant (RLQ) pain” as their inclusion criteria (19 studies, n = 7,510, AA prevalence = 42.8%, 95% CI = 41.7–43.9) compared to those that used “abdominal pain” or undifferentiated abdominal pain (two studies, n = 1,095, AA prevalence = 13.4%, 95% CI = 11.5–15.6).…”
Section: Resultsmentioning
confidence: 98%
“…Articles that only provided the final score with limited or no data on the variables were excluded . Twenty‐one studies were included in our review. The study selection process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations